PELATIHAN MEDIA PEMBELAJARAN INTERAKTIF DI SMP IT IBNU SINA MERAUKE - Putra, Don Jaya; Gebze, Delson Albert; Algiranto, Algiranto (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Ibnu Sina Middle School Merauke is one of the secondary schools in Merauke Regency which has been providing education and teaching since 2019. As a newly established school, one of the problems experienced by this school is the lack of use of the latest interactive learning media in the science learning process. Based on studies related to these errors, it was found that science learning in class still uses the conventional one-way lecture method so that science learning is considered boring and less interesting according to students. This has an impact on students' low science learning outcomes. It was then found that the minimal use of learning media in science learning was caused by teachers' lack of knowledge of interactive learning media that could be used in the science learning process in the classroom. So it is hoped that this service activity can introduce science teachers and other subject teachers at Ibnu Sina Middle School how to use web-based interactive learning media in the classroom learning process so that lessons become more interesting, more lively, more active and more meaningful which will have an impact. on improving students' science learning outcomes at school.